Globopilumnus fragaria, a new species of eriphiid crab (Crustacea: Decapoda: Brachyura: Xanthoidea) from the South China Sea, with a key to the genus Globopilumnus Balss, 1933 - Yang, S.-L. (2014)
Raffles Bulletin of Zoology